2018
DOI: 10.1177/1078390318763963
|View full text |Cite
|
Sign up to set email alerts
|

TeleMental Health: Standards, Reimbursement, and Interstate Practice

Abstract: Providers, including psychiatric advanced practice registered nurses, can use TMH to effectively address the growing need for mental health services, although regulatory, licensure, and clinical issues must be addressed prior to offering TMH services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Telemedicine supports the provision of healthcare for a variety of conditions (e.g., diabetes, hypertension, heart failure, cancer) [5][6][7][8][9], but its potential to shape the delivery of mental health care is undeniable. Systematic and meta-analytic reviews have demonstrated that mental health treatment delivered via telemedicine, or telemental health, is equally, and in some cases more, effective than treatment delivered in-person and results in higher patient satisfaction at reduced costs [10][11][12][13]. The effectiveness and satisfaction of telemental health treatment is likely to be due to its ability to alleviate physical (e.g., travel time, missed work, and financial costs) and socio-cultural (e.g., concerns relating to stigma) barriers that are notorious for impeding healthcare accessibility and continuity [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine supports the provision of healthcare for a variety of conditions (e.g., diabetes, hypertension, heart failure, cancer) [5][6][7][8][9], but its potential to shape the delivery of mental health care is undeniable. Systematic and meta-analytic reviews have demonstrated that mental health treatment delivered via telemedicine, or telemental health, is equally, and in some cases more, effective than treatment delivered in-person and results in higher patient satisfaction at reduced costs [10][11][12][13]. The effectiveness and satisfaction of telemental health treatment is likely to be due to its ability to alleviate physical (e.g., travel time, missed work, and financial costs) and socio-cultural (e.g., concerns relating to stigma) barriers that are notorious for impeding healthcare accessibility and continuity [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This work has often gone unreimbursed. Although psychotherapy and pharmacology services are billable with telehealth fee-for-service codes for beneficiaries of Medicare and a growing number of Medicaid and commercial payers 1820 , behavioral health care management has not historically qualified as a billable service in this regard. In the CoCM model, psychiatric consultants see a relatively small percentage of the total patient panel face-to-face, limiting their fee-for-service billing opportunities.…”
Section: Treatment - the Collaborative Care Modelmentioning
confidence: 99%
“…Telehealth is a viable option for many providers, so long as the right technologies are in place. According to a 2018 JAPNA article by Adams et al, telemental health has been shown to have comparable (or even sometimes better) outcomes when compared to in-person care. For a great overview of considerations when implementing telemental health, I encourage you to access this article.…”
mentioning
confidence: 99%